EARLY OPEN REDUCTION INTERNAL FIXATION OF IPSILATERAL "DISPLACED" SACRO-ILIAC FRACTURE PREVENT SHORTENING OF THE LIMB: RADIOLOGICAL EVALUATION (Proceedings of the International Conference of Community Health and Medical Sciences, 2024)
The Sacro-Iliaca is part of the pelvis. The prevalence of pelvic fractures due to high-energy injuries is 93.6%. 46.8% of all cases of pelvic fractures required surgery. Displaced sacro-iliac fractures can cause the pelvis to be vertically or rotationally unstable, including Tile's classification of type B or type C. Fractures of the ipsilateral “displaced” sacro-iliac often result in shortening of the involved limb or “Leg Length Discrepancy”. Inadequate and late treatment can cause shortening of the limbs that is difficult or cannot be corrected so that the patient is lame. Open Reduction Internal Fixation of the initial fracture is helpful for correction of “LLD”. Radiological evaluation through antero-posterior projection of the pelvic x-Ray is easy to do with a comparison of "reference points" on the right and left sides, namely: "Greater Sciatic Notch", "Articular Cartilage", "Greater Trochanter Femur", "Superior Lesser Trochanter Femur", “pubic arch”, before and after surgery. In the case of a male, bus attendant, colliding with a truck, was thrown off bus, unable to move his right leg. General condition, and vital sign are stable. Right gluteal edema, bruised, right leg exorotation and shortens (LLD). X-Ray Pelvis Antero-Posterior, showing the pelvis and proximal femur on the right side with "5 reference points" rotation and cranial shift. Comminuted fracture of the iliac bone with displacement of the sacro-iliac. Diagnosed with comminuted iliac fracture and sacro-iliac displacement. Open Reduction Internal Fixation with the plate screw was done within less than 48 hours. X-Ray Pelvis was conducted after the surgery, it was appeared that 5 reference points on the right and left sides were almost 100% identical.
Keywords: Internal Fixation; Radiological evaluation